2007
DOI: 10.1074/jbc.m705116200
|View full text |Cite
|
Sign up to set email alerts
|

Derepression of MicroRNA-mediated Protein Translation Inhibition by Apolipoprotein B mRNA-editing Enzyme Catalytic Polypeptide-like 3G (APOBEC3G) and Its Family Members

Abstract: The apolipoprotein B mRNA-editing enzyme catalytic polypeptide-like 3G (APOBEC3G or A3G) and its fellow cytidine deaminase family members are potent restrictive factors for human immunodeficiency virus type 1 (HIV-1) and many other retroviruses. A3G interacts with a vast spectrum of RNAbinding proteins and is located in processing bodies and stress granules. However, its cellular function remains to be further clarified. Using a luciferase reporter gene and green fluorescent protein reporter gene, we demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
100
2
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 113 publications
(111 citation statements)
references
References 53 publications
6
100
2
1
Order By: Relevance
“…We were especially interested in MOV10, which has been described as a novel component of Argonaute-associated RNP complex (9). Because A3G is also the Argonaute-associated protein and can counteract miRNA-mediated protein repression, we studied the interaction between A3G and MOV10 (11,12). As shown in supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We were especially interested in MOV10, which has been described as a novel component of Argonaute-associated RNP complex (9). Because A3G is also the Argonaute-associated protein and can counteract miRNA-mediated protein repression, we studied the interaction between A3G and MOV10 (11,12). As shown in supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A3G Counteracts miRNA-mediated Gene Silencing by Inhibiting the Interaction between MOV10 and AGO2-Our previous study has shown that A3G can counteract miRNA-mediated protein inhibition (12). To determine the details of the molecular mechanism, we placed one copy of mir25-and mir16-binding sites with either perfectly or partially complementary to their corresponding miRNAs into the 3Ј-UTR of the reporter gene.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations